Perancangan Aplikasi Media Pembelajaran Augmented Reality (AR) Pengenalan Struktur Lapisan Bumi berbasis Android Menggunakan Unity 3D - Azzahra, Putri; Sundari, Siti; Khairunnisa, Khairunnisa (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2024)
Augmented Reality to create a new environment by combining the interactivity of real and virtual environments in real time so that users feel that the environment created is real. The model used in this research refers to the MDLC (Multimedia Development Life Cycle) type development model with 5 stages, namely Concept, Design, Material Collecting, Assembly, Testing and Distribution. The conventional learning process has been transformed into a digital form. One example is learning media, learning media is an effort designed in the learning process where material that is difficult to understand becomes easier to understand. To make it look more interesting, this learning media is made in the form of Augmented Reality. The results of this scientific work produce an application for learning about the structure of the earth's layers in the form of 3D Augmented Reality based on android, where when designing researchers use blender, unity 3D and vuforia applications.